Producción intelectual en las aulas de la Universidad Estatal de Bolívar. - Castillo Solano, Karla Julissa (2023)
The research purpose consisted of analyzing, through hermeneutics and legal comparison, the regulations of the State University of Bolívar (UEB) regarding Intellectual Property (IP) rights and their mechanisms to guarantee them. The investigative orientation was mixed, relying on the quantitative in addition to the qualitative. Regarding the scope, it was a descriptive study, whose cross-section was located in the second and third quarters of the year 2022. The object of study was the UEB Intellectual Property Regulation. A survey was applied that had as a population the students of the university who were conducting research Among the main results it was obtained that 60% of the students indicated that they had received a workshop, induction or subject on intellectual property rights at the UEB . 74% were not aware that the UEB will have a free, non-transferable and non-exclusive license for the non-commercial use of the work created by them. It was concluded that, with respect to copyright, industrial property and plant varieties, the UEB complied with the necessary unification of internal legislation that regulates institutional research and its relationship with intellectual property. There is a framework for the generation of income for the university, without loss of academic freedom, coupled with the protection of IP rights. Key words: Intellectual property rights, Bolívar State University, Ecuador.